Mental processes and breathing during exercise - Takahiro Yunoki (Japanese Society of Physical Fitness and Sports Medicine, 2012)
Breathing during exercise is an important physiological function for maintaining homeostasis of hydrogen ion concentration ([H+]) in the internal environment. In general, ventilatory response during exercise is considered to be automatically (unconsciously) controlled depending on exercise intensity and the corresponding perturbation of neurohumoral factors. However, in awake humans, the act of performing physical exercise is coupled with conscious elements such as motivation, effort, and emotions. This means that ventilatory control during exercise is also inseparably linked to such mental processes. With regard to the indivisibility between ventilatory control and conscious elements, there has been increasing psychological and neurophysiological evidence supporting the importance of mental and behavior factors in addition to neurohumoral factors. Therefore, in this paper, previous studies, on the indivisibility of ventilatory control and conscious elements, were looked at, and the roles of mental processes in ventilatory control and [H+] homeostasis during exercise discussed.